STEAM-ORIENTED TRANSFORMATIONS IN ONLINE COLLABORATIVE LEARNING TO BOOST READING COMPREHENSION: A META-SYNTHETIC ANALYSIS - Novarita Novarita; Abdurrahman Abdurrahman; Cucu Sutarsyah; Budi Kadaryanto (University of Kuningan, 2025)
This meta-synthetic analysis shows that STEAM-based transformations within online collaborative learning environments significantly enhance students’ reading comprehension. Across the synthesized studies, STEAM integration—through inquiry-driven tasks, interdisciplinary problem-solving, and multimodal digital tools—consistently improved literal, inferential, and evaluative comprehension skills. These gains were closely linked to increases in learner engagement, motivation, and sustained collaboration, indicating that reading becomes more meaningful when embedded in authentic, interdisciplinary contexts. The findings highlight that effective STEAM-oriented online collaboration requires clear scaffolding, structured group roles, and technology that supports co-construction of meaning. Platforms enabling joint annotation, discussion, and reflection helped students interpret texts from multiple perspectives and build deeper understanding. The results align strongly with social constructivism, cognitive load theory, and multiliteracies, demonstrating that students learn best when reading is approached as an active, social, and multimodal process. Nevertheless, several challenges emerged, including uneven digital literacy, inconsistent group participation, and teacher readiness for facilitating interdisciplinary online learning. Addressing these limitations will require deliberate instructional design, accessible digital tools, and ongoing professional development. This study provides an integrated perspective on how STEAM-based online collaborative learning meaningfully supports reading comprehension. By synthesizing diverse evidence, it establishes a coherent framework for designing innovative, technology-enhanced reading instruction. Future research should explore long-term learning effects, scalable implementation models, and the potential of emerging AI tools to support STEAM-aligned collaborative literacy practices.